1993
DOI: 10.1149/1.2056184
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Stainless Steel by an Alternating Voltage Process

Abstract: An alternating-potential-step (AV) passivation process is described which has been applied in an acid medium to stainless steel type 304. The corrosion resistance as determined by open-circuit potential decay, recording of anodic polarization curves, and impedance spectra is greatly increased by the AV passivation process especially when a post-treatment in an inhibitor solution is added to the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The fitting results show that the protectiveness of the passive film increases when 0.1 and 0.3 V(rms) AVs are applied to the system. This phenomenon is consistent with findings of Kwiatkowski and Mansfeld, 21 who found that an alternating potential step (AV) passivation can significantly improve the corrosion resistance of stainless steels in acid media. As shown by Song et al, 22 the AV increased the thickness of the passivation film, which consequently resulted in an increase in corrosion protectiveness.…”
Section: Influence Of Avs On Passivation Behavioursupporting
confidence: 92%
“…The fitting results show that the protectiveness of the passive film increases when 0.1 and 0.3 V(rms) AVs are applied to the system. This phenomenon is consistent with findings of Kwiatkowski and Mansfeld, 21 who found that an alternating potential step (AV) passivation can significantly improve the corrosion resistance of stainless steels in acid media. As shown by Song et al, 22 the AV increased the thickness of the passivation film, which consequently resulted in an increase in corrosion protectiveness.…”
Section: Influence Of Avs On Passivation Behavioursupporting
confidence: 92%
“…Mansfeld et al (51)(52)(53) utilized an Alternating Voltage (AV) passivation process to form modified surface films resulting in enhanced corrosion resistant properties. They studied the effectiveness of AV passivation over DC passivation on Type 304 stainless steel in 0.5 M H 2 SO 4 .…”
Section: Passive Films Formed By Potential Cyclingmentioning
confidence: 99%
“…It greatly improves the corrosion resistance of austenitic stainless steels in some corrosive media [8][9][10], but has not been applied to duplex stainless steels. Therefore the purpose of the present investigation was to use it on duplex stainless steel and investigate its effect on the corrosion resistance, and on the morphology, chemical structure and electronic structure of the passive film thus formed.…”
Section: Introductionmentioning
confidence: 99%